Population Trends of Sugarcane Moth Borers and Their Larval Parasitoid, Cotesia flavipes Cameron (Hymenoptera: Braconidae) in Growing Sugarcane Plantations - Maneerat, Tewee; Suasa-ard, Wiwat (Agriculture and Natural Resources, 2015)
Sugarcane moth borers, Chilo infuscatellus Snellen, Chilo sacchariphagus (Bojer), Chilo tumidicostalis (Hampson), Scirpophaga excerptalis (Walker), and Sesamia inferens (Walker) are important and destructive insect pests attacking sugarcane crops in the sugarcane planting areas in central Thailand. In sugarcane fields, they are controlled by the endoparasitic wasp, Cotesia flavipes Cameron (Hymenoptera: Braconidae) which is an effective larval parasitoid of the sugarcane moth borers. In the present investigation, population trends of the sugarcane moth borers and C. flavipes were analyzed in four districts of Thailand in three successive years (2009–2011 sugarcane planting seasons). Sugarcane moth borers occurred throughout the studied planting locations. The population trends of the insect pests and their parasitoid, C. flavipes, were synchronized early in each planting season when the sugarcane was in the sprout emergence stage, and throughout the end of each season. The sugarcane plants gave rise to fluctuations reminiscent of the parasitism of the parasitoid C. flavipes, indicating the phenology of the plant and insect host generating mechanisms, respectively.